OC-136 Changes in the practice of liver resection for colorectal liver metastases over a 15-year period in a high-volume UK hepatobiliary unit. (28th May 2012) - Macutkiewicz, C; Briggs, C D; Hidalgo, E; Toogood, G J; Lodge, J P A; Prasad, K R
Abstract : Introduction: Colorectal cancer remains the second most common cause of cancer-related death in Europe and North America. More than 50% of patients develop liver metastases within their lifetime and liver resection remains their only chance of cure. Recent trends in liver surgery have favoured parenchyma-preserving liver surgery over traditional major hepatectomies. 1 The aim of this study was to investigate the trend in approach to liver surgery over a 15-year period at a high-volume hepatobiliary unit. Methods: A prospectively maintained database containing data for the resection of colorectal liver metastases was analysed from 1995 to 2010. Demographic data were extracted together with data on types of liver resection, morbidity and mortality rates, and major vs minor hepatectomies. Minor hepatectomy was defined as any resection up to three segments and major hepatectomy was more than three segments resected. Data displayed compare the three 5-year periods from: 1995 to 1999, 2000 to 2004 and 2005 to 2009. Results: A total of 1414 hepatectomies were undertaken from 1995 up to 2010. 172 resections were performed in 1995–1999, 570 in 2000–2004 and 672 in 2005–2009. Median age and range were as follows: 61 years (36–80 years) in 1995–1999, 65 years (32–87 years) in 2000–2004, and 65 years (23–91 years) in 2005–2009. Major vs minor hepatectomy ratio were as follows: 55:45 in 1995–1999, 45:55 in 2000–2004, and 33:67 in 2005–2009. Complication rates were as follows: 29.1% in 1995–1999, 23.5% in 2000–2004, and 15.9% in 2005–2009. Mortality rates were significantly reduced from 9.3% in 1995–1999, and 3.3% in 2000–2004, to 1.9% in 2005–2009 (P Conclusion: The trend in liver resection has been towards more segmentectomies and metastasectomies rather than the more traditional major anatomical resections. This has been associated with a decreased complication rate and a significantly reduced mortality rate. This may reflect not only improvements in technique and critical care management but also in the paradigm shift towards parenchyma-preserving liver surgery. Local recurrence and survival rates will dictate whether this is the optimal treatment. Competing interests: None declared. Reference: 1. von Heesen M, Schuld J, Sperling J, et al. Parenchyma-preserving hepatic resection for colorectal liver metastases. Langenbecks Arch Surg 2011.